PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI (Survei pada Pelanggan di Salon Mobil M2CW Karanganyar) - Lamidi, Dhisma Chrismastuty, Rahayu Triastity & (Universitas Slamet Riyadi, 2017)
Car Salon M2CW Karanganyar in an effort to increase customer loyalty strive toprovide optimal service quality to customers. The purpose of this study was to analyzethe significance of the effect of service quality and corporate image on customersatisfaction in Salon Car M2CW Karanganyar, analyze the significance of the influenceof service quality, corporate image and customer satisfaction to customer loyalty inSalon Car M2CW Karanganyar, analyze the significance of the impact of service qualityand corporate image of the customer loyalty mediated by customer satisfaction inKaranganyar M2CW Car Salon. This study used survey methods, the type of data usedquantitative and qualitative data, the data source used primary data and secondary data.The population in this study customers who use the services of the Car Salon M2CWKaranganyar, the sampling technique used purposive sampling technique, with a samplesize of 100 respondents. Data collection methods are used: questionnaires anddocumentation. Data analysis technique used to test the validity, reliability test, classicassumption test, and path analysis. In conclusion that: there was a significant effect ofservice quality on customer satisfaction in customer Car Salon M2CW Karanganyar, nosignificant influence of corporate image on customer satisfaction in customer Car SalonM2CW Karanganyar, no significant effect of service quality on customer loyalty in thecustomer Salon car M2CW Karanganyar, no significant influence of corporate image oncustomer loyalty in customers car Salon M2CW Karanganyar, no significant effect ofcustomer satisfaction on customer loyalty in customers car Salon M2CW Karanganyar,customer satisfaction mediates the impact of service quality on customer loyalty,customer satisfaction mediates the influence corporate image on customer loyalty.Keywords: quality of service, corporate image, customer satisfaction, customer loyalty.